2007
DOI: 10.3171/foc.2007.22.5.9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of tumor-related brain edema

Abstract: ✓Cerebral edema contributes strongly to symptoms associated with brain tumors. Although the introduction of corticosteroids has greatly simplified treatment of patients with newly diagnosed tumors, these drugs are associated with marked side effects during the long-term treatment that is often necessary in the recurrences. Therefore, a better understanding of mechanisms related to the evolution and clearance of tumor-related edema with the aid of modern imaging and molecular methodology is clearly nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(81 citation statements)
references
References 88 publications
3
70
0
8
Order By: Relevance
“…Weber et al (109) reported elevated Cho/NAA ratios in the perifocal T2-weighted hyperintense region in cases of gliomas but no in metastases, in accordance with our results. These results support the previous findings that peritumoral edema associated with HGGs is characterized by extensive infiltration of tumor cells (170), whereas peritumoral region in metastases contained no tumor cells or vascular endothelial proliferation but almost purely vasogenic edema (106,109,157,171). …”
Section: Mrsi In the Peritumoral Tumor Regionsupporting
confidence: 92%
See 1 more Smart Citation
“…Weber et al (109) reported elevated Cho/NAA ratios in the perifocal T2-weighted hyperintense region in cases of gliomas but no in metastases, in accordance with our results. These results support the previous findings that peritumoral edema associated with HGGs is characterized by extensive infiltration of tumor cells (170), whereas peritumoral region in metastases contained no tumor cells or vascular endothelial proliferation but almost purely vasogenic edema (106,109,157,171). …”
Section: Mrsi In the Peritumoral Tumor Regionsupporting
confidence: 92%
“…In other words, in metastatic tumors, there is no histologic evidence of tumor beyond the outer margin of the tumor (158,169). In contrast to edema surrounding metastases, peritumoral edema associated with HGGs is characterized by extensive infiltration of tumor cells (170). A recent paper by Engelhorn et al (168) showed that the so-called perifocal edema not only includes invading tumor cells but also is associated with glial alterations in vital brain tissue.…”
Section: Magnetic Resonance Perfusion In the Peri-enhancing Region: Gmentioning
confidence: 99%
“…Alterações intracranianas como edema, hidrocefalia e hemorragia podem ocorrer secundariamente (Kraft & Gavin 1999, Stummer 2007. Convulsão é o sinal neurológico mais comum em cães e gatos (Snyder et al 2006, Tomek et al 2006, mas recentemente relatou-se a alteração de consciência como o sinal clínico de maior ocorrência (Santos et al 2012).…”
Section: Introductionunclassified
“…12,27 Therefore, the peritumoral T2 prolongation of GBM is caused by a combination of vasogenic edema and tumoral infiltration simultaneously. 28 Further research demonstrated that the perifocal T2 prolongation of GBM not only includes invading tumor cells but also is associated with glial alterations in vital brain tissue. 29 These differences in the mechanism of peritumoral T2 prolongation formation may explain our finding that the peritumoral nSI of GBM is higher than that of MET.…”
Section: Figmentioning
confidence: 99%